2012
DOI: 10.1152/ajpheart.00955.2010
|View full text |Cite
|
Sign up to set email alerts
|

The onset of left ventricular diastolic dysfunction in SHR rats is not related to hypertrophy or hypertension

Abstract: Dupont S, Maizel J, Mentaverri R, Chillon JM, Six I, Giummelly P, Brazier M, Choukroun G, Tribouilloy C, Massy ZA, Slama M. The onset of left ventricular diastolic dysfunction in SHR rats is not related to hypertrophy or hypertension. Am J Physiol Heart Circ Physiol 302: H1524 -H1532, 2012. First published January 27, 2012; doi:10.1152/ajpheart.00955.2010.-Left ventricular (LV) diastolic dysfunction, particularly relaxation abnormalities, are known to be associated with the development of LV hypertrophy (LVH).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 46 publications
3
32
1
Order By: Relevance
“…To explore if the alteration of the early diastole could be in relation with a diastolic reticulum calcium capture abnormality, we explored the SERCA 2a mRNA expression. We did not observe any change at the mRNA level compared with WKYs animals but, a recent study reported a decrease in SERCA 2a protein with unchanged SERCA 2a mRNA expression [18], leading to changes in intracellular calcium homeostasis, main cause of LV diastolic dysfunction. In the same work, at cellular level, SERCA 2a mRNA expression was not significantly modified in SHRs.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…To explore if the alteration of the early diastole could be in relation with a diastolic reticulum calcium capture abnormality, we explored the SERCA 2a mRNA expression. We did not observe any change at the mRNA level compared with WKYs animals but, a recent study reported a decrease in SERCA 2a protein with unchanged SERCA 2a mRNA expression [18], leading to changes in intracellular calcium homeostasis, main cause of LV diastolic dysfunction. In the same work, at cellular level, SERCA 2a mRNA expression was not significantly modified in SHRs.…”
Section: Discussioncontrasting
confidence: 80%
“…The modification of these parameters, that mainly evaluate the early diastole, argues in favor of a reduction of the cardiomyocytes relaxation properties. Such dysfunction could appear as early as 3 weeks old in SHRs [18]. In a recent study investigating the time course of cardiac abnormalities in aortic-banded rats, Perlini et al [19] identified that alterations of the early diastole predict the progression of compensated pressure overload hypertrophy to heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that LV relaxation dysfunction and elevated [Ca 2ϩ ] i were observed before development of hypertension and hypertrophy in SHRs (14). These data suggest that rather than being a consequence of hypertrophy, enhanced I Na,L may contribute to Ca 2ϩ overload, causing the hypertrophic response observed in the SHR.…”
Section: )mentioning
confidence: 89%
“…These results are similar to changes observed in other experimental models of hypertension such as the genetic spontaneously hypertensive rat, in which LV dysfunction is also verified prior the BP increase. 16, 17 Dupont et al 16 recently showed that 3-week-old spontaneously hypertensive rat developed LV systolic dysfunction with decreased FS and impaired LV diastolic function, suggesting early diastolic dysfunction. In addition, in spontaneously hypertensive rat, interstitial fibrosis and LV hypertrophy accompany BP elevation at an adult age.…”
Section: Discussionmentioning
confidence: 99%